Covert regime change : America's secret Cold War - O'Rourke, Lindsey A. (Cornell studies in security affairs., 2018)
"This study is the first to systematically assemble an original dataset of all American regime change operations during the Cold War. The United States attempted more than 10 times more covert than overt regime changes. The author asks three questions: What motivates states to attempt foreign regime changes? Why do states prefer to conduct these operations covertly, as opposed to overtly? How successful are these missions in achieving their foreign policy goals?"--